Nanoparticle-based delivery of siDCAMKL-1 increases microRNA-144 and inhibits colorectal cancer tumor growth via a Notch-1 dependent mechanism - Ponnurangam Sivapriya; Qu Dongfeng; Mondalek Fadee G; May Randal; Sureban Sripathi M; Pantazis Panayotis; Anant Shrikant; Ramanujam Rama P; Houchen Courtney W (Journal of Nanobiotechnology, 2011)
Abstract Background The development of effective drug delivery systems capable of transporting small interfering RNA (siRNA) has been elusive. We have previously reported that colorectal cancer tumor xenograft growth was arrested following treatment with liposomal preparation of siDCAMKL-1. In this report, we have utilized Nanoparticle (NP) technology to deliver DCAMKL-1 specific siRNA to knockdown potential key cancer regulators. In this study, mRNA/miRNA were analyzed using real-time RT-PCR and protein by western blot/immunohistochemistry. siDCAMKL-1 was encapsulated in Poly(lactide-co-glycolide)-based NPs (NP-siDCAMKL-1); Tumor xenografts were generated in nude mice, treated with NP-siDCAMKL-1 and DAPT (γ-secretase inhibitor) alone and in combination. To measure let-7a and miR-144 expression in vitro, HCT116 cells were transfected with plasmids encoding the firefly luciferase gene with let-7a and miR-144 miRNA binding sites in the 3'UTR. Results Administration of NP-siDCAMKL-1 into HCT116 xenografts resulted in tumor growth arrest, downregulation of proto-oncogene c-Myc and Notch-1 via let-7a and miR-144 miRNA-dependent mechanisms, respectively. A corresponding reduction in let-7a and miR-144 specific luciferase activity was observed in vitro. Moreover, an upregulation of EMT inhibitor miR-200a and downregulation of the EMT-associated transcription factors ZEB1, ZEB2, Snail and Slug were observed in vivo. Lastly, DAPT-mediated inhibition of Notch-1 resulted in HCT116 tumor growth arrest and down regulation of Notch-1 via a miR-144 dependent mechanism. Conclusions These findings demonstrate that nanoparticle-based delivery of siRNAs directed at critical targets such as DCAMKL-1 may provide a novel approach to treat cancer through the regulation of endogenous miRNAs.